Computational vibrational study on coordinated nicotinamide - Bölükbaşı Yalçınkaya, Olcay; AKYÜZ, SEVİM (Elsevier, 2005)
The molecular structure and vibrational spectra of zinc (II) halide complexes of nicotinamide (ZnX2(NIA)2; X=Cl or Br; NIA=Nicotinamide) were investigated by computational vibrational study and scaled quantum mechanical (SQM) analysis. The geometry optimisation and vibrational wavenumber calculations of zinc halide complexes of nicotinamide were carried out by using the DFT/RB3LYP level of theory with 6-31G(d,p) basis set. The calculated wavenumbers were scaled by using scaled quantum mechanical (SQM) force field method. The fundamental vibrational modes were characterised by their total energy distribution. The coordination effects on nicotinamide through the ring nitrogen were discussed.
Keywords: DFT calculations; Nicotinamide; Zinc halide complexes; SQM force field vibrational spectra